Comparative Susceptibility of Pathogenic Methicillin-Resistant and Methicillin-Susceptible Staphylococcus pseudintermedius to Empirical Cotrimazole for Canine Pyoderma - Khongsri, Usasom; Chongrattanameteekul, Peerawit; Chantarachart, Sineenart; Photichai, Kornravee; Chanayat, Nittaya; Varinrak, Thanya; Mektrirat, Raktham; Srifawattana, Nuttawan (Life (Basel, Switzerland), 2023)
The prevalence of methicillin-resistant (MRSP) that causes pyoderma has been gradually shifting, according to many surveillance studies, with annual changes. The empirical cotrimazole regimen remains interesting, but research on cotrimazole susceptibility to MRSP is limited. The objective of this study was to evaluate the susceptibility of cotrimazole to canine pyoderma MRSP isolates. Sixty isolates of were identified as 16 MRSP and 44 methicillin-susceptible (MSSP) using an oxacillin disk diffusion test and VITEK 2 system with VITEK GP card. Using the VITEK 2 system with a VITEK AST-GP81 card, the susceptibility rates of MRSP (15.00%) and MSSP (35.00%) to cotrimazole was observed. The median MIC of cotrimazole on MSSP (median, ≤10; IQR, 10-320) was lower than that of MRSP (median, ≥320; IQR, 10-320) ( 0.5889, Mann-Whitney test). Percent attainment of PK/PD targets in MRSP (q 12 h, 43.75; q 8 h, 43.75) were lower than that of MSSP (q 12 h, 52.27; q 8 h, 52.27) ( = 0.7710). These findings show the moderately phenotypic cotrimazole susceptibilities of both MRSP and MSSP. Further study is required to develop clinical trials examining the use of cotrimazole in dogs with pyoderma.